2011
DOI: 10.1124/mol.110.069419
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Caveolin in Probucol-Induced Reduction in hERG Plasma-Membrane Expression

Abstract: The human ether-à -go-go-related gene (hERG) encodes the pore-forming subunit of the rapidly activating delayed rectifier K ϩ current (I Kr ) important for cardiac repolarization. Dysfunction of the hERG channel causes long QT syndrome (LQTS). Although diverse compounds reduce the hERG current (I hERG ) by blocking the channel, probucol, a cholesterol-lowering drug that causes LQTS, reduces I hERG by decreasing plasma-membrane hERG protein expression. Here, we investigated the mechanisms of probucol effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 39 publications
1
40
1
Order By: Relevance
“…Furthermore, we provide the first example of a therapeutic compound that arrests hERG maturation in a nonexportable form via binding to residues in the canonical drug-binding site of hERG. This is very different from what has been proposed for proarrhythmic compounds such as probucol or progesterone (Guo et al, 2011;Wu et al, 2011), which are thought to mediate changes in hERG surface expression via effects on the composition of lipid rafts surrounding the channel protein. The reliance of pentamidine on hERG-specific amino acid residues may also provide an answer to its specificity and may explain why pentamidine effects are restricted to ER export, because the native conformation of hERG that is present in post-ER compartments binds pentamidine with much lower affinity only.…”
Section: Drug-induced Trafficking Inhibition 207mentioning
confidence: 47%
See 1 more Smart Citation
“…Furthermore, we provide the first example of a therapeutic compound that arrests hERG maturation in a nonexportable form via binding to residues in the canonical drug-binding site of hERG. This is very different from what has been proposed for proarrhythmic compounds such as probucol or progesterone (Guo et al, 2011;Wu et al, 2011), which are thought to mediate changes in hERG surface expression via effects on the composition of lipid rafts surrounding the channel protein. The reliance of pentamidine on hERG-specific amino acid residues may also provide an answer to its specificity and may explain why pentamidine effects are restricted to ER export, because the native conformation of hERG that is present in post-ER compartments binds pentamidine with much lower affinity only.…”
Section: Drug-induced Trafficking Inhibition 207mentioning
confidence: 47%
“…However, channel endocytosis in combination with accelerated degradation has emerged more recently as an alternative mechanism used by proarrhythmic compounds to control hERG surface expression. For example, it has been shown that probucol, a cholesterol-lowering drug causing acLQTS, increased endocytic hERG uptake from the cell surface (Guo et al, 2011). A similar increase in endocytosis has been described upon exposure of hERG to low extracellular potassium concentrations (Guo et al, 2009).…”
Section: Discussionmentioning
confidence: 85%
“…This could be deleterious to hERG channels that are thought to localize to cholesterol-rich lipid rafts (48). A similar hypothesis has been proposed to explain how probucol, a drug known to deplete cellular cholesterol levels, may induce hERG endocytosis (41). On the other hand, hERG endocytosis cannot be induced by exposure to methyl-␤-cyclodextrin, a chelator often used to extract cholesterol from cell membranes (49).…”
Section: Discussionmentioning
confidence: 90%
“…To study the effect of carbachol on hERG degradation, BFA (10 mM) was used to block the conversion of hERG from the immature 135-kDa form to the mature 155-kDa form (Guo et al, 2009(Guo et al, , 2011a. The degradation rate of hERG was monitored by detecting the 155-kDa band expression level at different time points after BFA treatments in control and carbachol-treated cells.…”
Section: Muscarinic Receptor Modulation Of Herg Channelsmentioning
confidence: 99%